Effet du biochar issu de Quercus canariensis sur la croissance de Raphanus sativus et Lactuca sativa - Benzine Nesrine (My University, 2026)
This study evaluates the effect of biochar derived from oak (Quercus canariensis) on the germination and growth of radish (Raphanus sativus) and lettuce (Lactuca sativa), as well as the influence of pyrolysis temperature on its physicochemical properties. Biochars produced at 300 °C, 450 °C, and 700 °C were incorporated at rates of 5% and 10% into an inert substrate (construction sand) to rigorously isolate their impact on plant development. Physicochemical analyses show that increasing the pyrolysis temperature from 300 to 700 °C leads to a gradual increase in pH (from 7.67 to 10.55) and electrical conductivity (from 300 to 935 µS/cm), while the residual moisture content decreases (from 8.52% to 6.06%). Agronomic trials reveal that plant response depends heavily on the dose and type of biochar. The treatment produced at low temperature (300 °C) proves most favorable for total dry biomass accumulation, particularly at a 10% dose. Conversely, high-temperature biochars (450 and 700 °C) limit the Relative Root Mass Index (RRMI) in favor of above-ground growth, while ensuring excellent maintenance of tissue water balance. In conclusion, these results confirm that Quercus canariensis biochar is a promising soil amendment for optimizing substrate management. They suggest that a moderate pyrolysis temperature (300 °C) offers the best short-term agronomic efficiency for plant biomass production. ---------------------------------------------------------------------------------------------------------------------------------------------------------------------------------- تقيّم هذه الدراسة تأثير الفحم الحيوي المستخرج من بلوط (Quercus canariensis) على إنبات ونمو الفجل (Raphanus sativus) والخس (Lactuca sativa)، بالإضافة إلى تأثير درجة حرارة الانحلال الحراري على خصائصه الفيزيائية والكيميائية. تم دمج الفحم الحيوي المنتج عند 300 درجة مئوية و450 درجة مئوية و700 درجة مئوية بنسب 5٪ و10٪ في ركيزة خاملة (رمل البناء) لعزل تأثيره على نمو النبات بشكل دقيق. تُظهر التحليلات الفيزيائية والكيميائية أن زيادة درجة حرارة الانحلال الحراري من 300 إلى 700 درجة مئوية تؤدي إلى زيادة تدريجية في الرقم الهيدروجيني (من 7.67 إلى 10.55) والتوصيلية الكهربائية (من 300 إلى 935 ميكروسيمنس/سم)، بينما ينخفض محتوى الرطوبة المتبقية (من 8.52% إلى 6.06%). تكشف التجارب الزراعية أن استجابة النبات تعتمد بشكل كبير على جرعة ونوع الفحم الحيوي. أثبتت المعالجة المنتجة عند درجة حرارة منخفضة (300 درجة مئوية) أنها الأكثر ملاءمة لتراكم الكتلة الحيوية الجافة الإجمالية، خاصة عند جرعة 10٪. وعلى العكس من ذلك، فإن الفحم الحيوي المنتج عند درجات حرارة عالية (450 و700 درجة مئوية) يحد من مؤشر الكتلة الجذرية النسبية (RRMI) لصالح النمو فوق سطح الأرض، مع ضمان الحفاظ بشكل ممتاز على توازن الماء في الأنسجة. وختاماً، تؤكد هذه النتائج أن الفحم الحيوي المستخرج من شجرة Quercus canariensis يُعد مادة واعدة لتحسين التربة من أجل تحسين إدارة الركيزة. وتشير النتائج إلى أن درجة حرارة الانحلال الحراري المعتدلة (300 درجة مئوية) توفر أفضل كفاءة زراعية على المدى القصير لإنتاج الكتلة الحيوية النباتية. --------------------------------------------------------------------------------------------------------------------------------------------------------------------------------- Cette étude évalue l’effet du biochar issu de Chêne zéen (Quercus canariensis) sur la germination et la croissance du radis (Raphanus sativus) et de la laitue (Lactuca sativa), ainsi que l’influence de la température de pyrolyse sur ses propriétés physico-chimiques. Les biochars produits à 300 °C, 450 °C et 700 °C ont été incorporés à des doses de 5 % et 10 % dans un substrat inerte (sable de construction) afin d’isoler rigoureusement leur impact sur le développement des plantes. Les analyses physico-chimiques montrent que l’élévation de la température de pyrolyse de 300 à 700 °C entraîne une hausse progressive du pH (de 7,67 à 10,55) et de la conductivité électrique (de 300 à 935 µS/cm), tandis que le taux d’humidité résiduelle diminue (de 8,52 % à 6,06 %). Les essais agronomiques révèlent que la réponse des plantes dépend fortement de la dose et du type de biochar. Le traitement produit à basse température (300 °C) s'avère le plus favorable à l’accumulation de la biomasse sèche totale, particulièrement à la dose de 10 %. À l'inverse, les biochars de haute température (450 et 700 °C) limitent l'Indice de Masse Racinaire Relative (IMRR) au profit d'un investissement aérien, tout en garantissant un excellent maintien de l'équilibre hydrique des tissus. En conclusion, ces résultats confirment que le biochar de Quercus canariensis constitue un amendement prometteur pour optimiser la gestion des substrats. Ils suggèrent qu'une température de pyrolyse modérée (300 °C) offre la meilleure efficacité agronomique à court terme pour la production de biomasse végétale.
Keywords: Biochar; Quercus canariensis; Pyrolysis temperature; Raphanus sativus; Lactuca sativa.; الفحم الحيوي، Quercus canariensis، درجة حرارة الانحلال الحراري، Raphanus sativus، Lactuca sativa.; Température de pyrolyse; Lactuca sativ